El Nino and La Nina - Rose, Sally frey50; Weather Channel (Television station : Atlanta, Ga.) (New York : Simon Spotlight, 1999)
Identifies the causes of the phenomena known as El Nino and La Nina, the differences between them, and why each causes such weather extremes.
At head of title: The Weather Channel.
Includes index.
Keywords: Climatic changes; El Nino Current; La Nina Current; El Nino Current; La Nina Current